PERENCANAAN PARTISIPATIF MASYARAKAT PADA PROGRAM SOSIALISASI UPAYA ADAPTASI DAN MITIGASI PERUBAHAN IKLIM - Fauziah, Marisa; Septiani, Dena; Zalzabila, Adinda; Adriansya, Muhammad Naufal; Hikam, Farhan Fadlillah; Novitasari , Nastiti (Jurnal Pengabdian Masyarakat Indonesia, 2024)
This article contains community participatory planning in socialization programs for climate change adaptation and mitigation efforts. The introduction presents the context of the importance of addressing the impacts of global warming through active community involvement. With a focus on program implementation at Balai Dusun Cinyenang, Sidamulya Village, Cisaga District, Ciamis Regency, on April 24, 2024, this article highlights strategies implemented to increase community awareness, understanding, and participation in adaptation and mitigation efforts. The analysis describes participatory planning as the key to success, considering the elements that form the foundation framework in improving the effectiveness of socialization programs. It is hoped that this article can provide additional insight into the importance of community engagement in confronting the challenges of climate change.